2019
DOI: 10.3390/rs11030224
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Unmanned Aerial Vehicle Optical Imagery for Early Detection and Severity Assessment of Late Blight in Potato

Abstract: Assessment of disease incidence and severity at farm scale or in agronomic trials is frequently performed based on visual crop inspection, which is a labor intensive task prone to errors associated with its subjectivity. Therefore, alternative methods to relate disease incidence and severity with changes in crop traits are of great interest. Optical imagery in the visible and near-infrared (Vis-NIR) can potentially be used to detect changes in crop traits caused by pathogen development. Also, cameras on-board … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 107 publications
(90 reference statements)
1
46
0
1
Order By: Relevance
“…Image capture using mobile platforms (UAVs, ground robots etc) is being studied in the field, although disease detection is the primary focus (Johnson et al 2003;Garcia-Ruiz et al 2013;de Castro et al 2015). Measurement of severity with VIS spectrum image analysis using mobile platforms is less common (Lelong et al 2008;Sugiura et al 2016;Duarte-Carvajalino et al 2018;Franceschini et al 2019;Ganthaler et al 2018;Liu et al 2018), but is an area of research need. An automated VIS image analysis system on a UAV for measuring severity had moderate precision compared to visual rating (R 2 = 0.73), but was deemed acceptable for rating potato resistance to late blight (Sugiura et al 2016).…”
Section: Application In Research and Practicementioning
confidence: 99%
“…Image capture using mobile platforms (UAVs, ground robots etc) is being studied in the field, although disease detection is the primary focus (Johnson et al 2003;Garcia-Ruiz et al 2013;de Castro et al 2015). Measurement of severity with VIS spectrum image analysis using mobile platforms is less common (Lelong et al 2008;Sugiura et al 2016;Duarte-Carvajalino et al 2018;Franceschini et al 2019;Ganthaler et al 2018;Liu et al 2018), but is an area of research need. An automated VIS image analysis system on a UAV for measuring severity had moderate precision compared to visual rating (R 2 = 0.73), but was deemed acceptable for rating potato resistance to late blight (Sugiura et al 2016).…”
Section: Application In Research and Practicementioning
confidence: 99%
“…Pre-symptomatic disease detection using spectroscopic methods is a rapidly advancing frontier in plant pathology [18,19,[31][32][33][34][35]. Symptomatic late and early blight detection has been previously established with a range of broad-band optical sensors [36][37][38][39][40][41][42][43], though none have explored pre-symptomatic detection and importantly, differentiation, using narrowband SWIR features. As well, foundational leaf-level work is needed to assess the potential for spaceborne imaging spectroscopy for disease differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al [37] also showed that the multispectral optimized soil adjusted vegetation index (OSAVI) has a strong discriminating capability between healthy and diseased winter wheat plants. In addition, UAV imagery is able to detect changes in crop traits linked to disease incidence [39]. Therefore, high-resolution UAV remote sensing can be successfully applied for spatial explicit assessment of crop health as a consequence of the presence of century-old biochar within agricultural soils.…”
Section: Introductionmentioning
confidence: 99%